Literatur Review : Analisis Pemahaman Pasien Terhadap Sistem Rujukan Berjenjang Jaminan Kesehatan Nasional (JKN) - Mariani, Tia; Rahma, Shinta; Amira, Anisa Puti; Gurning, Fitriani Pramita (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Health is one of the basic human needs to be able to live a decent and productive life. For this reason, it is necessary to provide controlled health in terms of cost and quality, because every human being, rich or poor, living in developed or developing countries, is always faced with life-threatening risks at any time. The implementation of the referral system in Indonesia has been arranged in a tiered or tiered form, namely First, Second and Third Level Health Facilities, which in practice do not stand alone but are in a system and are interconnected. Until now the implementation of the tiered referral system is still being refined, especially related to the understanding of BPJS participants about the tiered referral system. Lots of participants who came to PPK I or PPK II did not understand the tiered referral mechanism. The method used in this study is the Literature Review method, which is a systematic, reproducible and explicit method for identifying, evaluating and synthesizing the works and ideas of researchers. The results obtained from the results of this study are that there are still many people or patients who still do not understand the tiered referral system in the National Health Insurance (JKN). after reviewing as many as 5 articles, it was concluded that there are still many people or patients who still do not understand the tiered referral system in the national health insurance (JKN). This is due to the understanding of health workers regarding the vertical referral system and the horizontal referral system and referral patients have never received socialization about the referral system, explanations from officers were obtained when requesting referrals and posters at the puskesmas. Keywords: JKN, Tiered Referral System, Patient Health